If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-2)+1/5=-6
We move all terms to the left:
2(x-2)+1/5-(-6)=0
We add all the numbers together, and all the variables
2(x-2)+6+1/5=0
We multiply parentheses
2x-4+6+1/5=0
We multiply all the terms by the denominator
2x*5+1-4*5+6*5=0
We add all the numbers together, and all the variables
2x*5+11=0
Wy multiply elements
10x+11=0
We move all terms containing x to the left, all other terms to the right
10x=-11
x=-11/10
x=-1+1/10
| -12=4(a-1) | | -2g+15=10 | | 10x+4=194 | | 4b+13=4-2b | | 9x+3-2x-6=11 | | 7a+2=0 | | 3(7n+13)=2(12n+15) | | 7r+2=5(r-4 | | 5(1.032x+1)=11 | | 5a-9=5a-15 | | c=-8+3c | | T=m² | | -8(4+s)=-48 | | 3(7n+13)=2(12n+15 | | 2p-3/5=7 | | (x-15)(-6)=-78 | | 25x+41=16x+23 | | -39=-8p-5p | | 60=-6(n-5) | | -5u=-6u–5 | | 7p−4=8 | | 18x-17=11x-10 | | 3(x-5)=2(x+2)+5x-22 | | 13-6d=-47 | | -7m+10=-5m | | -7j=-6j–5 | | -25x+120=-15x+80 | | 5^((x-3)(x+4))-(0.2^x)*25^(x-4)=0 | | 6(t+2)=90 | | x+(6x+10)(x+2)=180 | | 4p+8=3p | | -38+7x=6(4x |